2006
DOI: 10.1158/1535-7163.mct-06-0379
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of transforming growth factor-β-activated kinase 1 activity enhances TRAIL-induced apoptosis through activation of a caspase cascade

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL/Apo2L) is a member of the TNF-A ligand family that selectively induces apoptosis in a variety of tumor cells. To clarify the molecular mechanism of TRAILinduced apoptosis, we focused on transforming growth factor-B-activated kinase 1 (TAK1) mitogen-activated protein kinase (MAPK) kinase kinase, a key regulator of the TNF-A-induced activation of p65/RelA and c-Jun NH 2 -terminal kinase/p38 MAPKs. In human cervical carcinoma HeLa cells, TRAIL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Western blot analysis was performed as previously described (11). Cells were seeded and incubated overnight in a 60-mm culture dish (0.25x10 6 cells/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (11). Cells were seeded and incubated overnight in a 60-mm culture dish (0.25x10 6 cells/ml).…”
Section: Methodsmentioning
confidence: 99%
“…TRAIL activated TAK1 in HeLa cells resulting in p65, JNK and p38 activation; siRNA knockdown or chemical inhibition of TAK1 enhanced TRAIL-induced apoptosis. 68 The earlier mentioned activation of p38 by TRAIL in prostate cancer cells was preceded and dependent on activation of TAK1, leading to transcriptional upregulation of Mcl-1 and suppression of apoptosis. 59 Inhibition of TAK1 is an effective approach to increase TRAIL sensitivity as was reported by Morioka et al 69 , although in their study, direct phosphorylation of TAK1 after TRAIL was not demonstrated.…”
mentioning
confidence: 96%
“…We also performed experiments using the TAK1 inhibitor, 5Z-7-oxozeaenol. This compound is a resorcylic acid lactone of fungal origin, which has been shown to be a highly effective and specific inhibitor of TAK1 Choo et al, 2006). Pretreatment of cells with 5Z-7-oxozeaenol inhibited the phosphorylation of p38 (Fig.…”
Section: Resultsmentioning
confidence: 98%